The Role of Land Law in the Politics of Land Procurement Law for National Development - Sutarjo, Sutarjo (International Journal of Education, Information Technology, and Others, 2024)
Land is important for human life and on land humans make a living, besides that on land humans also build houses as shelter and build various other buildings for offices and so on. Land has a social function. Land in daily life has a very important role in human life because it can determine the existence and continuity of relationships and legal actions. Land also contains various kinds of natural wealth that can be utilized by humans. In essence, the meaning and strategic position of land in The life of Indonesian society not only contains physical aspects, but also social, economic, cultural, political, defense and security and legal aspects. Land for society has a multidimensional meaning. From an economic perspective, land is a means of production that can bring prosperity. Politically, land can determine a person's position in community decision making and as a culture it can determine the high or low social status of its owner. The role of land law in national development between public interests and ownership rights to land must be able to provide legal certainty, benefits in determining ownership of land rights and can avoid conflicts, because it is the basis of government policy in land acquisition in national development, so that land acquisition is determined for the public interest. Community land ownership rights determine whether a national development program can be implemented or not. Meanwhile, the legal politics of land acquisition in national development between the public interest and ownership rights to land is to be able to realize the objectives of the legal principles used as guidelines to realize the objectives already stated in the UUPA as the objectives and legal principles of article 33 paragraph (3) of the 1945 Constitution, but on the other hand The UUPA and its legal principles serve as a source for developing policies and legislation to ensure the realization of prosperity for all Indonesian people.